Evaluation of Attention to the Pattern of Iranian Muslim Woman in Content of Religion and Life Books in Lower Secondary Schools - Haghgoo, Razieh (2021)
The present study has been compiled in order to analyze the content of the textbooks of Religion and Life in lower secondary school for attention to the formation of the Iranian Muslim Woman Pattern. The main purpose of this study is to investigate the content of religion and life textbooks in the lower secondary school on explaining the characteristics of the Iranian Muslim Woman Pattern for female students. To achieve this goal, content of this books analysis with William Romey method and then data gathered with researcher-made questionnaire and analyzed the results with using SPSS24 statistical software. The statistical sample of the study includes 306 female students and 19 teachers of religion and life lesson in lower secondary school in 9th district of Tehran who were studying and teaching in public schools. Findings indicate that there is a significant difference in the views of students and teachers regarding the content of this books. In such a way that the students had a more favorable view of the content of this books in reaching the pattern of the Iranian Muslim Woman, while from the teachers' point of view, the content of this books does not help us enough to reach the pattern of the Iranian Muslim Woman. The results of the quantitative analysis by the researchers indicate that the content of three books of religion and life in lower secondary school is primarily in the category of “monotheism and theism”, “religious ethics”, “rules” and then “women, family and society”. And the content of the books is lacking in terms of guiding students to reach the pattern of Iranian Muslim Women.